2021
DOI: 10.4103/jehp.jehp_1139_20
|View full text |Cite
|
Sign up to set email alerts
|

Developing a health-promoting school using knowledge to action framework

Abstract: BACKGROUND: There is a lack of organized effort in the arena of school health promotion, which has been recognized as an effective approach to combat the growing incidence of communicable and noncommunicable diseases. With this view, a study was conducted to develop comprehensive and replicable model for health promotion in schools. MATERIALS AND METHODS: The Knowledge to Action (KTA) framework recognized by the World Health Organization as an implementational framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…According to stakeholders who participated in our survey, there is insufficient public awareness about the dangers of smoking and the provisions of COTPA. There is already evidence of low public knowledge and weak adherence to the legislation in India [27]. As a result, neither the individual nor society receive all of the advantages provided by the law [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to stakeholders who participated in our survey, there is insufficient public awareness about the dangers of smoking and the provisions of COTPA. There is already evidence of low public knowledge and weak adherence to the legislation in India [27]. As a result, neither the individual nor society receive all of the advantages provided by the law [28].…”
Section: Discussionmentioning
confidence: 99%
“…Dongre et al (2011) assessed the impact of the implementation of the HPS model post one year in ten schools. The authors reported improvement in hemoglobin level (from 10.7 g/dL to 11.4 g/dL, p = 0.001) and body mass Further, a recent study reported improved practice of healthy diets 2.6 to 5 times in children from lower classes compared to the higher classes due to of the implementation of HPS model (Jain et al, 2021). Collectively, the three studies indicated the potential of the HPS model to improve the food and nutrition outcomes in Indian school children and adolescents.…”
Section: A Comparative Analysis Of Nfsi Fssai and Iap Guidelinesmentioning
confidence: 95%
“…. study identified the following factors as barriers to the implementation: teachers' heavy schedules, academic and curricular priorities, specific allotted hours for health promotional activities for academic engagements, and the family culture of consumption of high-calorie foods (Jain et al, 2021). Together, the evidence indicated the beneficial effects of the implementation of the HPS model, however, the successful implementation would require additional human, educational and financial resources.…”
Section: A Comparative Analysis Of Nfsi Fssai and Iap Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation